Innovation within Indian Family Firms - Gupta, Mohit (2011)
The main focus of this research is to try and measure the importance of innovation within family firms in India. The different levels of importance given to fifteen factors important for innovation would be measured. Theories to highlight all these key participants and factors would be discussed. An attempt to analyze the difference between responses from first generation family business owners and either non-family managers or second generation family managers would also be done. A quantitative survey and a qualitative interview would be conducted to gather data for the research. This research would try and start a focus on research on this subject. Suggestions and limitations for this research would also be given for the future.